The billion dollar question: How much will it cost to decarbonise cities' transport systems? - Nicolas Wagner (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper puts numbers on the investment needs for urban transport infrastructure under different policy scenarios. The cities of the future will be shaped by today's decisions about physical transport assets, and the urgent need to halt climate change makes it more important than ever to get it right. The analysis shows that a low-carbon transport system is not necessarily more expensive than today's mobility system, and can even be more cost-efficient.
Keywords: 330